2018
DOI: 10.3126/nmcj.v20i4.25139
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Anxiety and Depression in Patient with Chronic Obstructive Pulmonary Disease

Abstract: Anxiety and depression are very common comorbidities in patients with chronic obstructive pulmonary disease (COPD). This study was aimed at documenting the prevalence anxiety and depression in COPD patient attending tertiary level hospital. A quantitative cross sectional analytical study was carried out in 221 patients with previously diagnosed COPD. Participants were recruited from respiratory OPD at Tribhuvan University Teaching Hospital, Nepal. Anxiety and depression were screened using previously validated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 13 publications
(15 reference statements)
1
7
1
Order By: Relevance
“…al. In present study reported pa ents lived in joint family prone to develop depression (p=0.046).This finding is consistent 7,15 with the result of previous studies.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…al. In present study reported pa ents lived in joint family prone to develop depression (p=0.046).This finding is consistent 7,15 with the result of previous studies.…”
Section: Discussionsupporting
confidence: 93%
“…A study was done in China showed that 7.2 % Depression and Anxiety 5.3% This study concluded that high prevalence 6 of anxiety and depression in COPD outpa ents. A study conducted in Kathmandu and Okhaldhunga, Nepal showed that 63.3%, 69.2% and 39.8% , 35.5% were suffered from 7,8 the anxiety and depression in the COPD pa ents. Nepal being a culturally diverse country, the impact of mental illness in health may vary in different communi es.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Similarly the study done in Tribhuvan University Teaching Hospital (TUTH), Kathmandu, Nepal revealed that patient's age, ethnicity, educational status, marital status, current working status, duration of illness, history of previous hospitalization were significantly associated with anxiety among the COPD patients. [14]…”
Section: Discussionmentioning
confidence: 99%
“…8 In addition, studies in Nepal shows the prevalence of diabetes mellitus (DM) type II is 29.2%, 9 among COPD patient is 69.2%. 10 In developing countries like Nepal, where health care facilities and human resources are limited, no conclusive research explains depression in this region. Therefore, the general objective of this research is to determine the prevalence and correlation of depressive symptoms in patients with chronic physical illness and relation to attributes of depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%